El papel del profesor-asesor en el prácticum de la Licenciatura en Educación Física, Recreación y Deporte (2020)
This article is based on the results of the research projects “Orientações pedagógicas no estágio supervisionado de educação física na Colômbia, Brasil, Argentina e Chile” and “Senses of the body modes and teaching knowledge of the practicum in Physical Education, Recreation and Sports of the Universidad de Caldas”, motivated by the interest in understanding the role and characteristics of the teacher-advisor in the training of the practitioner-teacher, in the context of the practicum of the Bachelor’s Degree in Physical Education, Recreation and Sport. It is a research design supported by the qualitative approach, of historical-descriptive-hermeneutic nature, with multiple case study, in-depth interview techniques and documentary analysis. In this context, the results presented focus on the role of teacher-advisor from the reflection, action, orientation, advice and relationship with those involved in the practicum, to contribute to the knowledge of teaching practices, the role of teacher-advisor and the view of the practitioners-teachers on this, and how teaching knowledge come together facilitating didactic actions and strengthening the teaching identity.